2018
DOI: 10.1109/jlt.2018.2840489
|View full text |Cite
|
Sign up to set email alerts
|

Passively Mode-Locked Ytterbium-Doped Fiber Laser With Cylindrical Vector Beam Generation Based on Mode Selective Coupler

Abstract: We propose and demonstrate, for the first time to the best of our knowledge, a passively mode-locked ytterbium-doped fiber laser generating cylindrical vector beams (CVBs) using a mode selective coupler (MSC) as the transverse mode converter and splitter, and a semiconductor saturable absorber mirror (SESAM) for mode-locking. According to the coupling mode theory and the phase matching principle, the MSC was fabricated by weakly fused technology, having a low loss of about 0.5 dB and achieving LP11 mode with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Mode selective couplers (MSCs) are key components of future mode division multiplexing (MDM) optical networks [1,2], which could be used in a mode multiplexer/ demultiplexer [3][4][5][6][7], few-mode fiber lasers [8][9][10][11][12][13][14][15][16], etc. Usually, an MSC consists of a singlemode-fiber (SMF) and a few-mode-fiber (FMF) whose cores are brought close together.…”
Section: Introductionmentioning
confidence: 99%
“…Mode selective couplers (MSCs) are key components of future mode division multiplexing (MDM) optical networks [1,2], which could be used in a mode multiplexer/ demultiplexer [3][4][5][6][7], few-mode fiber lasers [8][9][10][11][12][13][14][15][16], etc. Usually, an MSC consists of a singlemode-fiber (SMF) and a few-mode-fiber (FMF) whose cores are brought close together.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Chen et al demonstrated an all-fiber actively mode-locked laser producing CVB pulses with high efficiency and a tunable repetition rate, where a two-mode long-period fiber grating (TM-LPFG) was introduced into the laser cavity as a mode converter and a two-mode fiber Bragg grating (TM-FBG) is used as a mode selector [18]. In 2018, Wan et al proposed a passively mode-locked CVB fiber laser using a mode selective coupler (MSC) as the transverse mode converter and a semiconductor saturable absorber mirror (SESAM) for mode-locking [19]. The pulse repetition rate is 18.58 MHz with the signal-to-noise ratio (SNR) of 52 dB.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic mode manipulation should be considered during generating spatial high-order modes (HOMs) directly, which can greatly improve the practical utilities of these light sources. Static methods of generating spatial modes in optical fibers can be mainly classified into four categories: mode selective couplers (MSCs) [29][30][31], photonic lanterns [32][33][34], long-period gratings (LPGs) [35][36][37][38] and fiber Bragg gratings (FBGs) [39][40][41]. MSC employs tapering fused fibers to demonstrate mode coupling via evanescent field interactions.…”
Section: Introductionmentioning
confidence: 99%